Simulation Model- A Tool for Improvement in Irrigation and Drainage Management in Brassica juncea (Mustard) at a Farmer's Field - Singh, Rajinder; Kumar, Jitender; Kumar, Rakesh (Journal of Agricultural Engineering, 2004)
Inefficient irrigation and drainage management, inadequate ground water pumpage and geohydrological condition has led to rise of water table in central and western part of Haryana state at a rate of 10 to 30 cm annually during the last three decades. The adopted irrigation practice in Brassica juncea (Mustard) at a farmer's field was evaluated with the help of simulation model SWASALT. The Water Management Response Indicators were used to evaluate the performance of irrigation practice. The study revealed that good crop performance (ETrel = 0.67) with 21.2% capillary contribution was achieved with irrigation supply of 21.5 cm as water table depth varied from 110-176 cm. The long term (5 years) extended simulations suggested that realizable yield of the crop (relative transpiration &gt 0.95) with more than 56% capillary contribution could be obtained with only one pre-sown irrigation of 8 cm and 2.2 cm rainfall if sub-surface drainage system installed at 1.50 m depth and 100 m spacing.